Lucan und der Prinzipat Inkonsistenz und unzuverlässiges Erzählen im Bellum Civile - Kimmerle, Nadja (Millennium-Studien / Millennium Studies, 2015)
Lucan`s Bellum Civile (Pharsalia) is traditionally read as a political critique of the Principate. However, several features of this text run counter to this interpretation. This study reexamines Lucan`s work using the model of the unreliable narrator to illuminate its portrayal of contradictory structures in Nero`s Principate. The interdisciplinary approach offers a new perspective on Lucan`s epic poem and its historical importance.